PENYULUHAN HASIL UJI SAMPEL AIR SUMUR SESUAI BAKU MUTU DAN PENGELOLAANNYA BAGI WARGA DUSUN SEDAYU 1, DESA SEDAYU, MUNTILAN, MAGELANG - Dewi Wahyuningtyas; Sri Rahayu Gusmarwani (DHARMA BAKTI, 2020)
Water is a vital need for human life. As a country that is rich in minerals, groundwaterin Indonesia often contains high levels of iron (Fe) and manganese (Mn). In water, these twometals are always together. For humans both metals are important, but can also be toxic(poisonous). Their presence in water can be detected laboratorally and can be recognizedorganoleptically. With Fe or Mn concentration of at least 1 mg/L, the water tastes bittersour,smells bad and is brownish yellow in color. In Sedayu 1 Hamlet, Sedayu Village,Muntilan, residents complained about the appearance of brownish water in their wells. Thiswas suspected because of the Fe and Mn metals content which exceed the standard quality.Therefore, water sample testing was carried out in three locations (well water 1, well water2, and pond water) in the area. Some of the parameters tested were hardness, pH, Fe andMn metal content. The test results then were socialized to 30 residents. The value ofhardness, Fe and Mn metals in several locations were still above the permitted qualitystandards. The residents were motivated to be more wary in the water treatment. The simplemethod for processing of water contaminated with metals were by adding activated carbonadsorbents and a heating process before it can consumed directly by residents.